ANALISIS STRATEGI PEMASARAN PERUSAHAAN MODAL VENTURA DI TENGAH PANDEMI COVID-19(Studi Kasus Pada PT.Sarana Lampung Ventura) - Defrizal Defrizal; Elvira Nasution (Jurnal Manajemen dan Bisnis (JMB), 2021)
Abstract This study aims to determine the marketing strategy of venture capital companies, to remain able to print company profits and to find out the factors that can hinder the implementation of marketing strategies in the midst of the COVID-19 Pandemic. This type of research is qualitative research. the source of data in this study is the result of interviews at PT. Sarana Lampung Ventura. Data collection methods used are preliminary surveys, interviews and documentation. The result of this research is PT. SLV changes its marketing strategy. PT. SLV cooperates with Third Parties, binds cooperation agreements, conducts marketing to prospective business partners with the category of MSMEs that have potential, conducts marketing to prospective business partners remotely.